PENGARUH TIPE KEPRIBADIAN DAN LINGKUNGAN BELAJAR TERHADAP MINAT BELAJAR SISWA DIKELAS XI SMA NEGERI 1 MOTOLING BARAT - Ranti, Devyano; Rumokoy, Johny; Bella, Valeria T (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine the influence of personality type and learning environment as a whole on students' learning interest in SMA Negeri 1 Motoling Barat. The research method used is the survey method, which is sourced from data and information obtained from respondents as research samples. The population in this study were all students of class XI at Sma Negeri 1 Motoling Barat totaling 50 students. The data collection technique used was random sampling with a level of 5% so that the sample obtained was 44 students. The results of the study showed that the personality type variable had a positive or significant influence on students' learning interest in SMA Negeri 1 Motoling, the learning environment variable had a positive or significant influence on students' learning interest in SMA Negeri 1 Motoling Barat, and the personality type variable, the learning environment variable together had a positive or significant influence on students' learning interest in SMA Negeri 1 Motoling Barat. Keywords: Personality Type, Learning Environment, Student Learning Interest